GENDER REPRESENTATION OF PERCY JACKSON & THE LIGHTNING THIEF IN ENGLISH AND INDONESIAN - Khoirida, Aina; Dewi, Haru Deliana (English Review: Journal of English Education, 2024)
Abstract: Children’s literature plays an essential role in shaping readers’ characters through the influence of the ideology implied in it. Children will learn and implement these ideologies as the target readers for their future lives. This study aims to find out the gender representation in one of the children’s literatures, Percy Jackson & the Lightning Thief, by Rick Riordan. By applying corpus linguistics, the number of characters and their representations are examined and compared between the English version as the source text and its Indonesian translation. The results show that although male characters dominate the novel in terms of number, a deeper analysis of the collocation of body parts with verbs reveals that there was a shift in gender representation between the two versions of the novel that have different cultural backgrounds. Furthermore, it was found that the author depicted some characters with less fixation on their sex; male characters are less masculine, and female characters are more masculine than the prevailing gender stereotypes in society. In the translated version, the translator rectified the stereotypes by depicting the characters’ gender according to sex. These findings reflect broader cultural ideologies about gender for the millions of readers who enjoy this book. In addition, these findings imply the significance of parents' and educators' awareness and critical thinking regarding the selection of reading materials for children.Keywords: children literature; corpus linguistic; critical discourse analysis; gender representation; translation